1990
DOI: 10.1002/jbm.820241004
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cell adhesion by modification of titanium surfaces with covalently attached self‐assembled monolayers

Abstract: The surface of titanium has been modified by covalent attachment of an organic monolayer anchored by a siloxane network. This coating completely covers the metal and allows controlled modification of surface properties by the exposed chemical endgroups of the monolayer forming surfactant. The attachment of such a film allows different bulk materials (e.g., glass and titanium) to have identical surface properties and this can be used in regulating cell adhesion responses. This control over surface functionality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…Since then many studies in neuronal patterning have been performed in a variety of labs, using various methods, including surface modification by silane chemistry 113 137 Ti, 140 polystyrene, 130,131 Teflon (fluorinated ethylene propylene), [132][133][134][141][142][143][144] and biodegradable polymers. 145 These studies mainly yielded insights into the adhesion and guidance of neuronal growth by insoluble factors and could prove valuable for selective neuronal immobilization on future microsensors.…”
Section: Vb Neuronal Cell Biology On a Chipmentioning
confidence: 99%
“…Since then many studies in neuronal patterning have been performed in a variety of labs, using various methods, including surface modification by silane chemistry 113 137 Ti, 140 polystyrene, 130,131 Teflon (fluorinated ethylene propylene), [132][133][134][141][142][143][144] and biodegradable polymers. 145 These studies mainly yielded insights into the adhesion and guidance of neuronal growth by insoluble factors and could prove valuable for selective neuronal immobilization on future microsensors.…”
Section: Vb Neuronal Cell Biology On a Chipmentioning
confidence: 99%
“…[31][32][33] Silane-modified surfaces have been widely utilized as model surfaces for biological interactions, including protein adsorption [34][35][36] and cellular and bacterial adhesion. [37][38][39] However, previous reports of cellular responses to silanated surfaces generally have been restricted to short-term studies of endothelial cells or fibroblast cell lines and have not yet addressed many of the significant cell-biomaterial interactions that occur throughout the duration of the inflammatory stage. Therefore, our investigation focuses on the dynamic interactions between silane-modified glass and freshly isolated human peripheral blood monocytes as an in vitro model for the monocyte-macrophage- Figure 1.…”
Section: Introductionmentioning
confidence: 98%
“…The density and mobility of recognition centres are therefore important design parameters during development of biosensing interfaces. The impact of surface chemistry on protein adsorption also has been demonstrated on several occasions using various types of SAMs, not just on gold but on Si, Ti and glass as well [7,[10][11][12][13]. Prime et al, for example, investigated the protein resistance of flexible long-chain oligo(ethylene) oxide modified SAMs [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of longer versus shorter alkyl chains it is believed that thermodynamics play a major role for the phase behavior [16,17]. Bain et al studied a series of mixed SAMs from HS -(CH 2 ) 11 -CH 3 /HS -(CH 2 ) n -CH 3 (n= 15,21) adsorbed from ethanol and isooctane [18]. Using contact angle measurements, ellipsometry, and XPS they concluded that macroscopic islands do not form in these monolayers.…”
Section: Introductionmentioning
confidence: 99%